TRANSFORMASI MANAJEMEN SDM DI ERA AI: STRATEGI UPSKILLING, KESEJAHTERAAN HOLISTIK, DAN KEPEMIMPINAN DIGITAL UNTUK MENINGKATKAN KETAHANAN ORGANISASI - Aslan Aslan; Dasa Rahardjo Soesanto (CV. Adiba Aisha Amira, 2026)
The transformation of human resource (HR) management in the era of artificial intelligence (AI) has become a strategic imperative for organisations seeking to maintain resilience and competitiveness amidst increasingly widespread technological disruption. This article aims to outline HR transformation strategies through the integration of three key pillars: adaptive upskilling, holistic well-being, and digital leadership. The research method employed is qualitative, utilising a literature review approach. The findings indicate that AI-based upskilling strategies enable the precise identification of competency gaps and personalised learning, thereby enhancing the effectiveness of talent development. Holistic well-being, which integrates physical, mental, emotional, social, and financial dimensions, has been proven to foster psychological safety and employees’ adaptive capacity in the face of uncertainty. Digital leadership acts as a catalyst bridging technological potential with the realisation of organisational resilience through the creation of a culture of continuous learning and ethical human-AI collaboration. The synergy of these three elements forms a virtuous cycle that continuously strengthens organisational resilience. This article concludes that organisational resilience in the AI era is no longer determined by technological infrastructure alone, but by the quality of human capital and the leadership that manages it strategically and humanely.